1996
DOI: 10.1007/bf00266823
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel lumbar disc herniation in 12-year-old twins

Abstract: Herniation of a lumbar disc in the pediatric age group is rare. A 12-year-old female twin developed backache and left sciatica after a mild lifting injury. Magnetic resonance imaging of the spine showed multilevel lumbar disc herniation. The patient was managed conservatively and her symptoms subsided within 6 weeks. Magnetic resonance imaging of her asymptomatic twin sister revealed a similar pattern of disc degeneration and multilevel herniation. This report emphasizes the hereditary nature of juvenile lumba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
9
0
5
Order By: Relevance
“…26) A 12-year-old girl with multilevel disc herniation was treated conservatively, and the patient's asymptomatic twin sister had herniated discs at several levels, corroborating the idea of a genetic predisposition. 20) A study of 40 patients with intervertebral disc herniation requiring surgical management and their parents compared them to a control group, finding a familial predisposition with an odds ratio of 5.61 as compared to the controls. 18) The present study identified a valid family history in 121 patients (73.3%) and a positive history in 82 of these (67.8%).…”
Section: Discussionmentioning
confidence: 99%
“…26) A 12-year-old girl with multilevel disc herniation was treated conservatively, and the patient's asymptomatic twin sister had herniated discs at several levels, corroborating the idea of a genetic predisposition. 20) A study of 40 patients with intervertebral disc herniation requiring surgical management and their parents compared them to a control group, finding a familial predisposition with an odds ratio of 5.61 as compared to the controls. 18) The present study identified a valid family history in 121 patients (73.3%) and a positive history in 82 of these (67.8%).…”
Section: Discussionmentioning
confidence: 99%
“…A hérnia discal ocorre principalmente entre a quarta e quinta décadas de vida (idade média de 37 anos), apesar de ser descrita em todas as faixas etárias (5)(6)(7)(8) . Estima-se que 2 a 3% da população possam ser afetados, com prevalência de 4,8% em homens e 2,5% em mulheres, acima de 35 anos.…”
Section: Epidemiologiaunclassified
“…Estudos demonstram que o limiar de sensibilização neuronal para uma raiz comprimida é cerca da metade do dos segmentos não comprimidos (21,22) . Existe uma diferença nos níveis de infiltração celular inflamatória em hérnias discais extrusas e não extrusas, menores nestas últimas (6,7) . Acredita-se que a ruptura do ligamento longitudinal posterior pelas hérnias extrusas as expõe ao leito vascular do espaço epidural, e células inflamatórias originadas desses vasos na periferia do material discal herniado podem ter um papel importante na irritação da raiz nervosa e na indução da dor ciática.…”
Section: Patogênese Da Ciáticaunclassified
See 1 more Smart Citation
“…Juvenile LDH cases in monozygotic twins that required operation were described by Matsui et al 19) . Obukhov et al also reported multilevel LDH in 12-year-old twins 20) . Sambrook et al compared Magnetic Resonance Imaging (MRI) features of degenerative disc disease in the cervical and lumbar spine of 172 monozygotic and 154 dizygotic twins 21) .…”
mentioning
confidence: 96%